19 electron NbCoSb thermoelectric material and preparation method and application thereof

Through high-energy ball milling method and discharge plasma sintering technology, the problems of complex preparation and difficult component control of NbCoSb thermoelectric materials in the existing technology were solved, and high-performance and low-thermal conductivity of 19 electronic NbCoSb thermoelectric materials were obtained, achieving the improvement of thermoelectric performance and production of thermoelectric properties. Simplification of the process.

CN119194146APending Publication Date: 2024-12-27NORTHWESTERN POLYTECHNICAL UNIV

Patent Information

Application Number
CN202411366876.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing methods for preparing NbCoSb thermoelectric materials are complex and difficult to accurately control the alloy composition, resulting in poor thermoelectric performance and inability to achieve large-scale production.

Method used

The Nb, Co, Sb elemental powders were mechanically alloyed by high-energy ball milling method to obtain nano-scale compound precursor powder, and then sintered in a discharge plasma sintering furnace, avoiding stoichiometric losses in traditional arc smelting and accurately controlling the alloy composition.

Benefits of technology

The preparation of high-performance thermoelectric materials is realized, the Seebeck coefficient and power factor are improved, the thermal conductivity is reduced, and the good high-temperature stability and high-purity products are obtained, which simplifies the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194146A_ABST
    Figure CN119194146A_ABST
Patent Text Reader

Abstract

The invention discloses a 19-electron NbCoSb thermoelectric material and a preparation method and application thereof, and particularly relates to the field of thermoelectric materials. Comprising the steps that Nb elementary substance powder, Co elementary substance powder and Sb elementary substance powder are placed in a high-energy ball mill to be subjected to mechanical alloying, and nanoscale NbCoSb compound precursor powder is obtained; the ball milling time of the high-energy ball mill is 12-24 hours; the nanoscale NbCoSb compound precursor powder is screened; and putting the screened nanoscale NbCoSb compound precursor powder into a graphite mold, and putting the graphite mold into a discharge plasma sintering furnace for sintering to obtain the N-type NbCoSb thermoelectric material. A large number of multi-scale nano structures and defects are introduced into the precursor, low thermal conductivity can be obtained while the electrical transport property is maintained, and then the high-performance thermoelectric material with good high-temperature stability is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of thermoelectric materials, and in particular to a 19-electron NbCoSb thermoelectric material and a preparation method and application thereof. Background Art

[0002] Nuclear power supply systems are not affected by the surrounding environment, are safe and reliable, and can provide electricity to spacecraft in a sustainable and stable manner. They are expected to solve the problem of providing continuous and stable power to satellites and spacecraft under harsh environmental conditions such as insufficient solar radiation, extreme low temperatures, high radiation belts, and dust storms. Nuclear power supply systems mainly include three parts: heat source, thermoelectric conversion system, and heat dissipation system. The thermoelectric conversion system converts the thermal energy generated by the heat source into electrical energy to supply power to external loads. The thermoelectric conversion system includes two thermoelectric conversion methods: static conversion and dynamic conversion. In practical applications, the geometric structure, safety and reliability, controllability, mission cycle, and post-maintenance of the system are comprehensively considered. It is evaluated that the thermoelectric conversion method based on the Seebeck effect of thermoelectric materials, which is a type of static conversion, is the best.

[0003] Thermoelectric materials are a class of functional materials that use the movement of carriers inside solids to achieve direct conversion between thermal energy and electrical energy. The performance of thermoelectric materials is usually characterized by the dimensionless thermoelectric figure of merit ZT, ZT = (S2σ / κ)T, where S is the Seebeck coefficient, σ is the electrical conductivity, κ is the thermal conductivity, and T is the absolute temperature. Since these thermoelectric parameters are coupled to each other through the carrier concentration, an excellent thermoelectric material must strike a balance between the conflicting requirements of high Seebeck coefficient, high electrical conductivity, and low thermal conductivity. Although substantial progress has been made in the field of thermoelectric materials over the past few decades, Half-Heusler (HH) compounds have received special attention as a promising medium- and high-temperature thermoelectric material due to their excellent high-temperature stability, low toxicity, good mechanical properties, and thermoelectric performance. HH compounds have a MgAgAs type crystal structure and belong to the F4_3m space group. Their chemical formula is ABX, where A is a transition metal element of IVB and VB groups, such as Ti, Zr, Hf, V, Nb, etc.; B is a transition metal element of Group VIII, such as Fe, Co, Ni, etc.; X is an element of Group IVA and VA, such as Sn, Sb, etc. Both theoretical and experimental studies have revealed the important influence of the valence electron number (VEC) on the electronic structure and physical properties of HH compounds. VEC = 18 is considered to be necessary for the semiconductor band gap to separate the bonding and antibonding states. It is generally believed that only the 18-electron HH compounds in the bonding state are particularly stable, while for the 17-electron and 19-electron HH compounds, since the bonding state will not be fully occupied or the antibonding state will be partially occupied, the bond interaction is weakened and different space groups are formed. However, 19-electron NbCoSb breaks the traditional theory and exhibits unique properties. It still maintains the cubic HH structure and still has a band gap at the bottom of its conduction band, which makes it expected to become a thermoelectric semiconductor. However, there is relatively little research on NbCoSb as a thermoelectric material.

[0004] So far, arc melting is still the mainstream method for preparing NbCoSb materials, consistent with other processes for synthesizing HH compounds. However, this method is difficult to operate, has a long production cycle, and inevitably has stoichiometric losses, which makes it difficult to accurately control the alloy composition, cannot achieve large-scale production, and the thermoelectric performance of the prepared products is relatively poor. At the same time, there is also a method for preparing NbCoSb materials through solid-state sintering. Although it avoids the problems existing in arc melting, it still needs to be further ball-milled and hot-pressed into blocks on the basis of vacuum sealing and solid-state sintering in the early stage, and the preparation process is relatively complicated. Summary of the invention

[0005] The main purpose of this application is to provide a 19-electron NbCoSb thermoelectric material and its preparation method and application, aiming to solve the problem of complex process of existing preparation methods.

[0006] To achieve the above-mentioned purpose, the present application provides a novel method for preparing 19-electron NbCoSb thermoelectric material, comprising: placing Nb single substance powder, Co single substance powder, and Sb single substance powder in a high-energy ball mill for mechanical alloying to obtain nano-scale NbCoSb compound precursor powder; wherein the ball milling time of the high-energy ball mill is 12~24h; the nano-scale NbCoSb compound precursor powder is screened; the screened nano-scale NbCoSb compound precursor powder is loaded into a graphite mold, and placed in a spark plasma sintering furnace for sintering, the sintering temperature is 1200K~1350K, and the sintering time is 10~20min, to obtain N-type NbCoSb thermoelectric material.

[0007] Optionally, in the high-energy ball mill, the grinding ball diameter is 2-12 mm, the ball-to-material ratio is 5-15:1, and the rotation speed is 400-500 r / min.

[0008] Optionally, the particle size of the sieved nano-scale NbCoSb compound precursor powder is 200-900 nm.

[0009] Optionally, the molar ratio of Nb single substance powder, Co single substance powder and Sb single substance powder is 1:1:0.95~1.05.

[0010] Optionally, the purity of the Nb single substance powder, the Co single substance powder, and the Sb single substance powder are all greater than 99.95%.

[0011] Optionally, the vacuum degree of the spark plasma sintering furnace is less than 10 -5 , pressure is 30~50MPa; heating rate is 50~200K / min, cooling rate is 50~200K / min, and the diameter of the graphite mold is 10~40mm.

[0012] The present application also provides a novel 19-electron NbCoSb thermoelectric material, which is obtained by using the above-mentioned method for preparing the novel 19-electron NbCoSb thermoelectric material.

[0013] The present application also provides an application of a novel 19-electron NbCoSb thermoelectric material in a thermoelectric conversion system.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The novel 19-electron NbCoSb thermoelectric material preparation method of the present invention ball-mills Nb single substance powder, Co single substance powder, and Sb single substance powder to achieve mechanical alloying. The collision of high-speed grinding balls can give the powder strong kinetic energy. The reasonable ball-to-material ratio, rotation speed and ball-milling time are conducive to grain refinement and obtain intermetallic compound precursors. At the same time, mechanical alloying can introduce a large number of multi-scale nanostructures and defects in the precursor, such as point defects, dislocations, grain boundaries, nanoparticles, etc., which can effectively scatter phonons in a wide spectrum range while increasing the electron carrier concentration inside the material to a certain extent. Therefore, low thermal conductivity can be obtained while maintaining electrical transport properties, thereby obtaining high-performance thermoelectric materials with good high-temperature stability; compared with the traditional arc melting method for preparing Half-Heusler thermoelectric materials, this method avoids the problem of stoichiometric loss caused by element evaporation in the process of high-temperature melting of elements with different melting points, and can accurately control the alloy composition to obtain high-purity products. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a comparison chart of the XRD spectra of a novel 19-electron NbCoSb thermoelectric material preparation method of this application and the NbCoSb product obtained by the existing method; Figure 2 The SEM microscopic morphology and composition analysis diagram of a novel 19-electron NbCoSb thermoelectric material preparation method of this application; Figure 3 This is a comparison chart of the conductivity of a novel 19-electron NbCoSb thermoelectric material preparation method of this application and the NbCoSb product obtained by the existing method; Figure 4 This is a comparison chart of the Seebeck coefficients of a novel 19-electron NbCoSb thermoelectric material preparation method of this application and a NbCoSb product obtained by an existing method; Figure 5 This is a power factor comparison diagram of a novel 19-electron NbCoSb thermoelectric material preparation method of this application and a NbCoSb product obtained by an existing method; Figure 6 This is a comparison chart of the thermal conductivity of a novel 19-electron NbCoSb thermoelectric material preparation method of this application and a NbCoSb product obtained by an existing method; Figure 7 This is a comparison chart of the ZT values ​​of a novel 19-electron NbCoSb thermoelectric material preparation method of this application and the NbCoSb product obtained by the existing method.

[0016] The realization of the purpose, functional features and advantages of this application will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical solutions and advantages of this application clearer, the technical solutions in this application will be clearly and completely described below in conjunction with the drawings in this application. Obviously, the described embodiments are part of the embodiments of this application, not all of them. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0018] The first embodiment of the present invention provides a method for preparing a novel 19-electron NbCoSb thermoelectric material, which specifically comprises the following steps: Step S1, according to the molar ratio of 1:1:0.95-1.05, Nb single substance powder, Co single substance powder, and Sb single substance powder are placed in a stainless steel ball mill, sealed, and placed in a high-energy ball mill for mechanical alloying to obtain a nano-scale NbCoSb compound precursor powder; wherein the ball milling time of the high-energy ball mill is 12-24h; in the high-energy ball mill, the grinding ball diameter is 2-12mm, the ball-to-material ratio is 5-15:1, and the rotation speed is 400-500r / min. The purity of the Nb single substance powder, the Co single substance powder, and the Sb single substance powder is greater than 99.95%.

[0019] Ball milling is performed on Nb single powder, Co single powder, and Sb single powder to achieve mechanical alloying. The collision of high-speed grinding balls can give the powder strong kinetic energy. A reasonable ball-to-material ratio, rotation speed, and ball milling time are conducive to grain refinement and obtaining intermetallic compound precursors. At the same time, mechanical alloying can introduce a large number of multi-scale nanostructures and defects in the precursor, which can obtain low thermal conductivity while maintaining electrical transport properties, thereby obtaining high-performance thermoelectric materials with good high-temperature stability.

[0020] Step S2, screening the nano-scale NbCoSb compound precursor powder; Specifically, in order to further ensure the uniformity of the powder, before screening, the partially agglomerated precursor powder after ball milling is manually crushed. The manual crushing method can be to grind it with an agate mortar for 10 to 30 minutes, and then use a 100 to 500 mesh sieve to sieve the ground nano-scale NbCoSb compound precursor powder to obtain a powder with a particle size uniformly distributed in 200 to 900 nm.

[0021] The weighing and sealing in step 1 and the grinding and sieving in step 2 are all performed in a glove box protected by argon gas with a water content of ≤5 ppm and an oxygen content of ≤5 ppm.

[0022] Step S3, the screened nano-scale NbCoSb compound precursor powder is loaded into a graphite mold with a diameter of 10-40 mm, and placed in a spark plasma sintering furnace for sintering. Compared with the hot pressing sintering process with indirect heating by an external heat source, the spark plasma sintering directly acts on the raw material powder through a large pulse direct current, so that a large amount of Joule heat is instantly generated inside the powder, and an extremely high heating rate (up to 1000 K·min−1) can be obtained. The heating and cooling process can be quickly realized, the preparation time is greatly shortened, and the temperature gradient is reduced to the maximum extent. The nanostructure of the mechanical alloying precursor powder is retained, which is conducive to reducing the lattice thermal conductivity and obtaining a more uniform microstructure. The N-type NbCoSb thermoelectric material is obtained; during the sintering process, the temperature is increased to 1200K~1350K at a heating rate of 50~200K / min, and after keeping the temperature for 10~20min, the temperature is decreased to room temperature at a cooling rate of 50~200K / min; the vacuum degree of the spark plasma sintering furnace is less than 10 -5 , pressure is 30~50MPa.

[0023] Example 1 Step S1, weighing 4 g of Nb single substance powder, 2.5373 g of Co single substance powder, 5.2418 g of Sb single substance powder and a grinding ball with a diameter of 7 mm, respectively, putting them into a stainless steel ball milling jar at a ball-to-material ratio of 10:1, sealing them, and placing them in a high-energy ball mill at a speed of 450 r / min for 24 h to obtain a nano-scale NbCoSb compound precursor powder; Step S2, grinding with an agate mortar for 10 minutes, and then sieving the ground nano-scale NbCoSb compound precursor powder with a 200-mesh sieve to obtain a powder with a particle size uniformly distributed at 785 nm; Step S3, the screened nano-scale NbCoSb compound precursor powder is placed in a graphite mold with a diameter of 20 mm, and placed in a spark plasma sintering furnace for sintering at a sintering temperature of 1273 K, a pressure of 35 MPa, and a holding time of 15 min; the vacuum degree of the spark plasma sintering furnace is less than 10 -5 , and obtain N-type NbCoSb thermoelectric material.

[0024] The performance test of the N-type NbCoSb thermoelectric material obtained in this embodiment shows that the thermal conductivity, Seebeck coefficient and electrical conductivity at 982K are κ = 3.57 W·m-1K-1), S = 162.89 μV·K-1, and σ = 0.96×105S·m-1. According to ZT=(S2σ / κ)T, the ZT value of the product prepared in this embodiment is about 0.6 at 982K.

[0025] The NbCoSb thermoelectric material obtained in this embodiment is compared with the NbCoSb obtained by solid phase sintering and arc melting. Figures 1 to 7 .Depend on Figure 1 It can be seen that all the diffraction peaks of all samples match well with the cubic HH phase of NbCoSb (JCPDS51-1247, a = 0.5897 nm), and NbCoSb-based Half-Heusler compounds with cubic MgAgAs-type crystal structure and F4_3m space group can be obtained. Figure 2 It shows that the Nb, Co, and Sb elements in the NbCoSb thermoelectric material obtained in this embodiment are uniformly distributed. Figures 2 to 6 It is found that, compared with the thermoelectric performance of the product obtained by the traditional arc melting method (marked as "●" in the figure), the electrical conductivity of the product obtained by the preparation method of the present invention (marked as "▲" in the figure) is reduced, but the Seebeck coefficient is significantly improved, and the thermal conductivity is significantly reduced, and finally its power factor is significantly increased, so the ZT value of the product obtained in this embodiment is significantly improved; compared with the thermoelectric performance of the product obtained by the solid phase sintering method (marked as "■"), the electrical conductivity and Seebeck coefficient of the product obtained in this embodiment are not much different, so the power factor is not much different, but the thermal conductivity is reduced.

[0026] Example 2 Step S1, weighing 4 g of Nb single substance powder, 2.5373 g of Co single substance powder, 5.2319 g of Sb single substance powder and a grinding ball with a diameter of 6 mm, respectively, putting them into a stainless steel ball milling jar at a ball-to-material ratio of 10:1, sealing them, and placing them in a high-energy ball mill at a speed of 450 r / min for 12 h to obtain a nano-scale NbCoSb compound precursor powder; Step S2, grinding with an agate mortar for 15 minutes, and then sieving the ground nano-scale NbCoSb compound precursor powder with a 300-mesh sieve to obtain a powder with a particle size uniformly distributed at 679 nm; Step S3, the screened nano-scale NbCoSb compound precursor powder is placed in a graphite mold with a diameter of 20 mm, and placed in a spark plasma sintering furnace for sintering at a sintering temperature of 1273 K, a pressure of 35 MPa, and a holding time of 15 min; the vacuum degree of the spark plasma sintering furnace is less than 10 -5 , and obtain N-type NbCoSb thermoelectric material.

[0027] After testing, the thermal conductivity, Seebeck coefficient, and electrical conductivity of the N-type NbCoSb thermoelectric material obtained in this embodiment at 982K are κ = 4.35 W·m-1K-1), S = 163.75 μV·K-1, and σ = 0.98×105S·m-1. According to ZT=(S2σ / κ)T, the ZT value of the sample prepared in this embodiment is about 0.6 at 982K.

[0028] Example 3 Step S1, weighing 4 g of Nb single substance powder, 2.5373 g of Co single substance powder, 5.2308 g of Sb single substance powder and a grinding ball with a diameter of 6 mm, respectively, putting them into a stainless steel ball milling jar at a ball-to-material ratio of 10:1, sealing them, and placing them in a high-energy ball mill at a speed of 450 r / min for 24 h to obtain a nano-scale NbCoSb compound precursor powder; Step S2, grinding with an agate mortar for 10 minutes, and then sieving the ground nano-scale NbCoSb compound precursor powder with a 100-mesh sieve to obtain a powder with a particle size uniformly distributed at 843 nm; Step S3, the screened nano-scale NbCoSb compound precursor powder is placed in a graphite mold with a diameter of 20 mm, and placed in a spark plasma sintering furnace for sintering at a sintering temperature of 1223 K, a pressure of 35 MPa, and a holding time of 15 min; the vacuum degree of the spark plasma sintering furnace is less than 10 -5 , and obtain N-type NbCoSb thermoelectric material.

[0029] Example 4 Step S1, 4 g of Nb single substance powder, 2.5373 g of Co single substance powder, 5.2509 g of Sb single substance powder and a grinding ball with a diameter of 7 mm are weighed respectively, and are placed in a stainless steel ball milling jar at a ball-to-material ratio of 10:1, sealed, and placed in a high-energy ball mill at a speed of 450 r / min for 12 h to obtain a nano-scale NbCoSb compound precursor powder; Step S2, grinding with an agate mortar for 15 minutes, and then sieving the ground nano-scale NbCoSb compound precursor powder with a 100-mesh sieve to obtain a powder with a particle size uniformly distributed at 690 nm; Step S3, the screened nano-scale NbCoSb compound precursor powder is placed in a graphite mold with a diameter of 20 mm, and placed in a spark plasma sintering furnace for sintering at a sintering temperature of 1223 K, a pressure of 35 MPa, and a holding time of 15 min; the vacuum degree of the spark plasma sintering furnace is less than 10 -5 , and obtain N-type NbCoSb thermoelectric material.

[0030] After testing, the thermal conductivity, Seebeck coefficient, and electrical conductivity of the N-type NbCoSb thermoelectric material obtained in this embodiment at 982K are κ = 4.03 W·m-1K-1), S = 162.99 μV·K-1, and σ = 0.95×105S·m-1. The above measurement results are calculated according to ZT=(S2σ / κ)T, and the ZT value of the sample prepared in this embodiment is about 0.6 at 982K.

[0031] The second embodiment of the present invention provides a novel 19-electron NbCoSb thermoelectric material, which is obtained by the above-mentioned method for preparing the novel 19-electron NbCoSb thermoelectric material.

[0032] The third embodiment of the present invention provides a novel 19-electron NbCoSb thermoelectric material for use in a thermoelectric conversion system.

[0033] The above are only preferred embodiments of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A method for preparing a novel 19-electron NbCoSb thermoelectric material, characterized in that: include: The Nb single substance powder, the Co single substance powder and the Sb single substance powder are placed in a high energy ball mill for mechanical alloying to obtain a nano-scale NbCoSb compound precursor powder; wherein the ball milling time of the high energy ball mill is 12 to 24 hours; Screening the nano-scale NbCoSb compound precursor powder; The screened nano-scale NbCoSb compound precursor powder is loaded into a graphite mold and placed in a spark plasma sintering furnace for sintering at a sintering temperature of 1200K-1350K and a sintering time of 10-20min to obtain an N-type NbCoSb thermoelectric material.

2. The method for preparing the novel 19-electron NbCoSb thermoelectric material according to claim 1, characterized in that: In the high-energy ball mill, the diameter of the grinding balls is 2-12 mm, the ball-to-material ratio is 5-15:1, and the rotation speed is 400-500 r / min.

3. The method for preparing the novel 19-electron NbCoSb thermoelectric material according to claim 1, characterized in that: The particle size of the sieved nano-scale NbCoSb compound precursor powder is 200-900 nm.

4. The method for preparing the novel 19-electron NbCoSb thermoelectric material according to claim 1, characterized in that: The molar ratio of the Nb single substance powder, the Co single substance powder, and the Sb single substance powder is 1:1:0.95-1.

05.

5. The method for preparing the novel 19-electron NbCoSb thermoelectric material according to claim 1, characterized in that: The purity of the Nb single substance powder, the Co single substance powder, and the Sb single substance powder are all greater than 99.95%.

6. The method for preparing the novel 19-electron NbCoSb thermoelectric material according to claim 1, characterized in that: The vacuum degree of the spark plasma sintering furnace is less than 10 -5 , pressure is 30~50MPa; heating rate is 50~200K / min, cooling rate is 50~200K / min, and the diameter of the graphite mold is 10~40mm.

7. A novel 19-electron NbCoSb thermoelectric material, characterized in that: The novel 19-electron NbCoSb thermoelectric material is obtained by the preparation method of any one of claims 1 to 6.

8. Application of a novel 19-electron NbCoSb thermoelectric material in thermoelectric conversion systems.

Citation Information

Patent Citations

  • Preparation method of novel n-type thermoelectric material NbCoSb

    CN105219995A

  • 19-valence-electron n-type NbCoSbSn thermoelectric material and preparation method thereof

    CN106756423A

  • Preparation method of half-Heusler alloy block thermoelectric material

    CN107937749A

  • N-type thermoelectric material formed based on TiNiSb and Fe elementary substance alloying and preparation method thereof

    CN118510366A

  • Preparation method for nano skutterudite compound pyro electric material

    CN1594623A

Cited By

  • Rapid solid-phase synthesis method of molybdenum antimonide-based material

    CN119614929A

  • A rapid solid-phase synthesis method of molybdenum antimonide-based material

    CN119614929B